Gross Capital Flows by Banks, Corporates, and Sovereigns - Avdjiev, Stefan; Hardy, Bryan; Kalemli-Ozcan, Sebnem; Serven, Luis (World Bank, Washington, DC, 2018)
This paper constructs a new dataset of quarterly capital flows by sector and establishes four facts. First, the co-movement of capital inflows and outflows is driven by banks. Second, procyclicality of capital inflows is driven by banks and corporates, whereas sovereigns' external liabilities move acyclically in advanced and countercyclically in emerging countries. Third, procyclicality of capital outflows is driven by advanced countries' banks and emerging countries' sovereigns (reserves). Fourth, capital inflows and outflows decline for banks and corporates when global risk aversion increases, whereas sovereigns' flows show no response. These facts are inconsistent with a large class of theoretical models.